HEAVY METAL CONCENTRATION IN MARINE SEDIMENTS AND VEGETATION ( CALTHA PALUSTRVIS ) FROM RIVER RAMOS IN BAYELSA AND DELTA STATES OF NIGERIA (Biological Sciences - PJSIR, 2002)
Heavy metals concentration in marine sediments and vegetation from River Ramos have been studied . Metals such  as  arsenic, mercury , cadmium , lead , chromium , nickel , iron, copper and zinc were analysed u sing atomic absorption spectrometer (AAS). The levels of these metals were determined from top and bottom river sediments, side and middle vegetation The analytica l  results revealed that arsenic levels were high in all the samples. Secondly, the highest concentration  of metals were found on the top sediment (68.00mg/kg dry weight) and vegetation (64.90mg/kg dry weight). Other metals such as mercury , chromium, nickel and iron were found to have  high  levels. The  high  levels  of  the  above  mentioned heavy metals are the cause of pollution , the concentration due to other metals such as cadmium, lead , copper and zinc was low. The high accumulation of heavy metals in the matrics  are  d ue  to activities  of oil companies and geochemistry  of  rocks.